(untitled) (De Legibus - Law Journal, 2022)
The modern enlightenment ideology identified law with the law-norm and saw the individual as the demiurge of legality. Later, man gradually came to be seen as a person, the law became imperative and the law could no longer be re(con) ducted to this particular mode of objectification. It is this evolutionary path that is the subject of this brief writing, prompted by the recent bicentenary of the 1820 Liberal Revolution.